Asmaul Husna: Linguistic forms, theological meanings, pedagogical implications, and their equivalents in Indonesian translation - Murtadho, Nurul (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Viewed from their linguistic forms, Asmaul Husna are classified into the mubalaghah group, whose meanings require the addition of “Maha” (the All-/Omni-/the Most), and the non-mubalaghah group, without the word “Maha.” Out of 99 names, only 69 appear in the Qur’an with different frequencies, ranging from 1 to 138 occurrences. The implication of this fact for professional educators is the requirement of pedagogical competence, personality competence, and social competence. Based on five data sources, four variants of translation were identified, and shifts in form and meaning were found. However, according to Islamic theology, all names in Asmaul Husna must be translated using the word “Maha,” which indicates the perfection of divine attributes. Further research should be directed toward the study of Asmaul Husna in the Hadith of the Prophet.